2011
DOI: 10.1007/s10895-011-0870-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prototropic Reactions on the Absorption and Fluorescence Spectra of Methyl p-dimethylaminobenzoate and Its Two Ortho Derivatives

Abstract: The influence of prototropic reactions on the spectral characteristics of methyl p-dimethylaminobenzoate (I) and its o-methoxy (II) and o-hydroxy (III) derivatives has been studied using steady-state spectroscopic technique and quantum-chemical calculations. This study concerns the solvent-induced shift of the absorption, locally excited (LE) and intramolecular charge transfer (ICT) fluorescence bands in the neat tetrahydrofuran (THF) and its hydrochloric acid solutions at different HCl concentrations. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In previous reports [ 28 , 29 , 30 , 31 , 32 ], we have shown that the long-wavelength absorption band of the studied fluorophores in neat solvents consists of two electronic transitions and of different character: ππ* and charge-transfer (CT). Moreover, it is well established that molecule II dissolved in some media besides the locally-excited (LE) fluorescence exhibits the long-wavelength emission from the excited-state intramolecular proton transfer (ESIPT) state [ 28 , 29 , 30 , 31 , 32 ]. In Figure 1 B,C, the long-wavelength absorption and fluorescence spectra of BSA in the phosphate buffer are compared with those of I and II .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous reports [ 28 , 29 , 30 , 31 , 32 ], we have shown that the long-wavelength absorption band of the studied fluorophores in neat solvents consists of two electronic transitions and of different character: ππ* and charge-transfer (CT). Moreover, it is well established that molecule II dissolved in some media besides the locally-excited (LE) fluorescence exhibits the long-wavelength emission from the excited-state intramolecular proton transfer (ESIPT) state [ 28 , 29 , 30 , 31 , 32 ]. In Figure 1 B,C, the long-wavelength absorption and fluorescence spectra of BSA in the phosphate buffer are compared with those of I and II .…”
Section: Resultsmentioning
confidence: 96%
“…We have recently undertaken spectroscopic investigations of the some methyl benzoate derivatives which, on the one hand, are interesting from the spectroscopic point of view (they are capable of exhibiting Twisted Intramolecular Charge Transfer- and/or Excited State Intramolecular Proton Transfer-type behaviour) and, conversely, they have potential in applications e.g., TICT and ESIPT fluorescence probes, metal ion sensors, active materials in dry xerographic toners or lasing medium in proton transfer lasers [ 28 , 29 , 30 , 31 , 32 ]. Our scientific attention has been focused not only on the description of the TICT and ESIPT processes of organic molecules in different organic solvents and heterogeneous systems, but also in aqueous solution in the presence of the supramolecular compounds (α-, β- and γ-cyclodextrins, cucurbit[7]uril) [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%